Screened Anxieties: Affect and Temporality in The Birth of a Nation. Issue 2 (May 2019) - DeJong, Tim
Abstract : This essay examines attitudes toward the future in D. W. Griffith's film The Birth of a Nation, focusing in particular on the opposed emotions hope and fear. In doing so, it establishes critical connections between the film's aesthetic philosophy – which is marked by an attempt to control its characters, its audience, and even history itself – and the film's troubling and much-discussed racial politics. Griffith's stated beliefs in the ability of cinema to fully capture the past and in turn to dictate to its audience the terms of the future, manifest themselves everywhere in The Birth of a Nation not only thematically but formally. However, the film sets an impossible task for itself, and where it falls short, its own hopes and fears become dramatically visible. This failure indicates that The Birth of a Nation is ultimately imbricated in the modernist episteme of uncertainty it works to deny and disavow.